Microbiological Profile And Antibiotic Susceptibility Pattern Of Uropathogens Isolated Among Cancer Patients At A Tertiary Care Cancer Centre, South India - Saravanan Murugesan, M.Sc, Ph.D; Sajani Samuel, Ph.D; Parthiban Rudrapathy, Ph.D. (International Journal of Pharma and Bio Sciences, 2020)
The purpose of the study is to analyze the microbiological profile and to study their antibiotic susceptibility patterns of uropathogens causing Urinary tract infections (UTIs) in cancer patients. In the current study, etiological and antimicrobial susceptibility profiles of urine cultures over a period of 2 year at a tertiary cancer care hospital was analyzed. Microbial and its antibiotic profile of the urine culture samples were retrieved from the microbiology laboratory data register. Identification and susceptibility testing of these uropathogens was performed by using automated VITEK 2 Compact system. A total of 3169 urine samples studied in which significant bacteriuria was seen in 705 (22%) patients. Of the 705 positive cultures, Gram negative bacilli accounted for 557 (79%), Gram-positive cocci for 112 (16%) and Candida species for 36 (5%). Among the Gram-negative pathogens, the most prevalent organisms isolated were Escherichia coli (43%) followed by Klebsiella pneumoniae (28.5%). In Gram-positive isolates, Enterococcus spp. (60%; Enterococcus faecalis = 39% and E. faecium= 17%) was the predominant species followed by Staphylococcus spp. [28.5%; coagulase-negative staphylococci (CoNS) = 16% and S. aureus = 12.5%]. Susceptibility of Gram-negative bacteria to amikacin was highest (76%) followed by the carbapenems (75%). Resistance was found to be higher to the aminoglycosides (47%), cephalosporins (65%) and fluoroquinolones (70%). Out of the total 14 S. aureus isolates, 57% were MRSA. All the Gram-positive isolates were found to be susceptible to vancomycin and linezolid. This study emphasizes the need for hospital or regional antibiograms to frame antimicrobial stewardship in order to combat and control the problem of antibiotic resistance, thereby helping clinicians to select appropriate antibiotic therapy for these immunosuppressed patients.